STRUCTURAL DAKWAH STRATEGY OF THE LOCAL GOVERNMENT OF SAMBAS POST CONFLICT OF SAMBAS ETHNICITY IN WEST KALIMANTAN - Irawan, Deni; Amin, Muliati; Ali, Baharuddin; Said, Nurman (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This writing specifically ellaborates the structural dakwah strategy of the Sambas Local Government post conflict. This is a qualitative-based research with sociological and communication approach. The data source of this research comes from the Ministry of Religions, Local Government, Religious Harmony Forum (FKUB), Indonesian Council of Ullemas (MUI) Sambas Regency, Sambas Muslim Forum TQN, religious and public figures in Sambas. Also, people who presumably can give information related to this topic. All data is collected through observation, interviews, and documentation. Data is analyzed through 4 stages of processess; data reduction, data presentation, data verification and conclusion. Fact-check process is using triangulation, reference books, and applying member check. The result of this research shows that the structural dakwah strategy, in which the local government FKUB, and MUI are in charge of, is performing the strategy throughout several religious prorgram. It is aligned with the regent of Sambas vision that has been determined in RPJMD 2016-2021 (the government masterplan). For example, building the life quality of religious community, providing hajj service facilites, providing religious consultancy, empowering houses of Quran in the districts, conducting preach during Ramadan, reciting on Magrib (dusk time), and visiting people’s house programme. There are also another program such as young preachers recruitment, non-civil servant consultant, and empowering people and religious teachers to preserve the community post conflict in the places where the social religious problems threaten the community.